Harnessing apomictic reproduction in grasses : what we have learned from paspalum - Ortíz, Juan Pablo Amelio (2013)
Fil: Ortíz, Juan Pablo Amelio. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.